2023
DOI: 10.1021/acs.nanolett.3c03171
|View full text |Cite
|
Sign up to set email alerts
|

Piconewton Forces Mediate GAIN Domain Dissociation of the Latrophilin-3 Adhesion GPCR

Brian L. Zhong,
Christina E. Lee,
Vipul T. Vachharajani
et al.

Abstract: Latrophilins are adhesion G-protein coupled receptors (aGPCRs) that control excitatory synapse formation. Most aGPCRs, including latrophilins, are autoproteolytically cleaved at their GPCR-autoproteolysis inducing (GAIN) domain, but the two resulting fragments remain noncovalently associated on the cell surface. Force-mediated dissociation of the fragments is thought to activate G-protein signaling, but how this mechanosensitivity arises is poorly understood. Here, we use magnetic tweezer assays to show that p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…24,28 Our study shows that a 1 pN/s loading rate results in conserved GAIN domain partial unfolding over pN forces for all three aGPCRs tested by comparing mechanical properties across subfamilies B, G, and L. Additionally, GPR56 and LPHN1 display extensive GAIN domain partial unfolding before NTF/CTF dissociation. In addition to the investigations of GPR56, LPHN1, and BAI3 presented in this work, the mechanical response of another aGPCR, LPHN3, has been studied by Zhong et al 59 They also observed a similar partial unfolding event that precedes the NTF/CTF dissociation at similar forces. These findings indicate that GAIN domain mechanosensitivity during physiological stretching is likely a conserved property among aGPCRs.…”
Section: ■ Direct Visualization Of Gain Domain Cleavage During Cell M...mentioning
confidence: 77%
“…24,28 Our study shows that a 1 pN/s loading rate results in conserved GAIN domain partial unfolding over pN forces for all three aGPCRs tested by comparing mechanical properties across subfamilies B, G, and L. Additionally, GPR56 and LPHN1 display extensive GAIN domain partial unfolding before NTF/CTF dissociation. In addition to the investigations of GPR56, LPHN1, and BAI3 presented in this work, the mechanical response of another aGPCR, LPHN3, has been studied by Zhong et al 59 They also observed a similar partial unfolding event that precedes the NTF/CTF dissociation at similar forces. These findings indicate that GAIN domain mechanosensitivity during physiological stretching is likely a conserved property among aGPCRs.…”
Section: ■ Direct Visualization Of Gain Domain Cleavage During Cell M...mentioning
confidence: 77%
“…This characteristic holds promise for a variety of applications. In addition to shedding light on the time scales involved in specific mechanotransduction processes at cell–matrix adhesions, cell–cell adherence junctions, and mechanical activation of T-cells, , they may also be applied to study the tension duration of various mechanically sensitive membrane receptors, such as adhesion GPCRs , and tethered ion channels . Moreover, the potential of dual-stretch-mode TGTs to significantly augment the utility of TGTs as mechanical instruments in DNA nanotechnology and bioengineering is considerable.…”
Section: Discussionmentioning
confidence: 99%
“…71,85,86 The intricate, modular architectures of aGPCRs likely evolved to withstand and react to strict spatial and force requirements in order to mediate intracellular events. 3,7,[87][88][89][90][91] More experimental structures of aGPCRs with larger extracellular regions, such as ADGRV1 or ADGRG4, as well as comprehensive mechanistic studies including structural biology, adhesion, and signaling activities, will determine whether the CMM is a general structural feature of adhesion GPCRs.…”
Section: An Updated View Of Adhesion Gpcr Structure and Function: The...mentioning
confidence: 99%